Pemberdayaan Perempuan Melalui Teknologi Roll Work 3-D Berbasis Limbah Kertas Di Nagari Lareh Nan Panjang Sungai Sariak - Olly Norita Tetra; Bustanul Arifin; Deswati Deswati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
3-Dimensional Roll Work technology training by processing waste paper into high-value handicraft products has been carried out in Nagari Lareh Nan Panjang, Padang Pariaman Regency. Most of the productive age groups in this area were unemployed women who depend on their husband's income for a living. In other hand, the activities of women's farmer groups, youth groups and (Family Welfare Movement) PKK were not productive. This activity aims to foster and empower community groups, especially women, in managing and processing paper waste into high selling value products with 3-Dimensional Roll Work technology that can be used as business opportunities so as to increase household income. The activity began with counseling on the dangers of paper waste for health and the environment, and continued by 3-dimensional Roll Work training. The indicator of the achievement of the targeted community service program was the management and processing of paper waste where each participant can produce quality handicraft products, namely key chains and accessories, while for other handicraft products, it was continued for group activities such as tissue, accessories, and cake boxes. This activity can be used as a sustainable empowerment effort through increasing community participation, self-financing and community self-help so as to create economically independent women in Nagari Lareh Nan Panjang.